Evaluation of sulfated maltodextrin as a novel anionic chiral selector for the enantioseparation of basic chiral drugs by capillary electrophoresis. Issue 2 (14th November 2014) - Tabani, Hadi; Mahyari, Mojtaba; Sahragard, Ali; Fakhari, Ali Reza; Shaabani, Ahmad
<x xml:space="preserve">Abstract</x> Introducing a new class of chiral selectors is an interesting work and this issue is still one of the hot topics in separation science and chirality. In this study, for the first time, sulfated maltodextrin (MD) was synthesized as a new anionic chiral selector and then it was successfully applied for the enantioseparation of five basic drugs (amlodipine, hydroxyzine, fluoxetine, tolterodine, and tramadol) as model chiral compounds using CE. This chiral selector has two recognition sites: a helical structure and a sulfated group which contribute to three corresponding driving forces; inclusion complexation, electrostatic interaction, and hydrogen binding. Under the optimized condition (buffer solution: 50 mM phosphate (pH 3.0) and 2% w/v sulfated MD; applied voltage: 18 kV; temperature: 20°C), baseline enantioseparation was observed for all mentioned chiral drugs. When instead of sulfated MD neutral MD was used under the same condition, no enantioseparation was observed which means the resolution power of sulfated MD is higher than neutral MD due to the electrostatic interaction between sulfated groups and protonated chiral drugs. Also, the countercurrent mobility of negatively charged MD (sulfated MD) allows more interactions between the chiral selector and chiral drugs and this in turn results in a successful resolution for the enantiomers. Furthermore, a higher concentration of neutral MD (approximately five times) is necessary to achieve the equivalent resolution compared with the negatively charged MD.